Human and the Element of the Soul in the perspective of Sufistic Psychology - Sawitri, Utari (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The study of western psychology and Islamic psychology has an interesting discourse about humans as the main object of study. Both in the western concept and the Islamic concept, the study of humans will never end considering that humans are dynamic, speculative, and fluctuating creatures. This study aims to examine humans and the various important elements that exist in them. This research is conducted through the Library Research method or literature study from several sources that rely on Sufistic experts such as Al-Ghazali. The results of the literature study concluded that humans in the expert's view are creatures that have the substance of body and spirit, both of which are connected to the substance of the soul which also has crucial elements in it such as Qalb, Aql, and Nafs, each of which has a level in it.